PEMAKAIAN CO2 SEBAGAI REFRIGERAN - Adriansyah, Willy; Bredesen, Arne M; Neksa, Petter (Mesin, 1997)
In the present situation there is a tendency to avoid as far as possible the use of the synthetic substances as refrigerant which can destroy ozone layer and increase average contribute to the A much more safe philosophy must be to revert to natural refrigerants, substances which are already present in our environment. The use of C02 as refrigerant is one attempt to this approach. This new refrigeration technology use special cycle called âLorentzen Cycle